Esther Balogh: On the Road to Biotechnology - Jaine, Tom (Petits Propos Culinaires, 2024)
Esther Balogh: On the Road to Biotechnology: Obafemi Awolowo University Press, Ile-Ife, 1999: ISSN 0189-7848: 46 pp., b/w illus., p/b, no price given.